Diversification of activity as a component of adaptive strategic management of construction enterprise - Yuanyuan Li; Biloshchytska, Svitlana (КНУБА, 2019)
The paper describes the strategy of diversification of construction enterprises. Their advantages and disadvantages are highlighted. The necessity of diversification of enterprises for increase of profits, reduction of risks and expansion of competitive opportunities is established. It was found that diversification of construction companies is relevant due to the significant development of the construction industry in the last decade in Ukraine, China and the world. The task of adaptive enterprise management in the part of creating diversification strategies is to conduct an analysis of the enterprise and the conditions in which the company operates. The scheme of analysis of the construction company for the implementation of diversification strategies is presented.
Keywords: construction enterprise; diversification; adaptive strategic management; the department information Technology Designing and Applied Mathematics; 69.003:005.21